Internalisasi Budaya Arab Melalui Pengenalan Ta’bir Arab Dalam Pembelajaran Maharah Al-Kalam - Astina, Chairani; Rahman, Rifqi Aulia; Nurbayan, Yayan; Burdah, Ibnu (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2024)
Maharah al-Kalam is the ability to express ideas or thoughts through articulated sounds with the aim of conveying understanding through two-way communication using language as the medium. In the context of learning Arabic, maharah al-kalam is one of the fundamental skills that students must master. However, most students face difficulties in speaking Arabic due to various factors, such as nervousness while speaking, lack of vocabulary mastery, limited practice, strong influence of local dialects, and monotonous teaching methods. The method used in this study is a literature review, and the data collection techniques employed by the author are documentation and literature study. In qualitative data analysis, the author utilizes content analysis. The objective of this study is to examine and describe how Arab culture can be internalized through the introduction of Arabic expressions (Ta’bir Arab) in Arabic language learning. This article will also provide examples of several expressions that can be introduced to students in teaching maharah al-kalam.